2022
DOI: 10.1021/acs.jafc.1c08047
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Absorption and Metabolism of the Tomato Imidazole Alkaloids N-Caprylhistamine-β-glucoside and N-Caprylhistamine

Abstract: Histamine-based imidazole alkaloids N-caprylhistamine (HmC 8 ) and N-caprylhistamine-β-glucoside (HmC 8 -Glc) were recently identified as precursors for a tomato biomarker. As studies regarding metabolism and bioavailability are scarce, the present study aimed at the elucidation of intestinal absorption and metabolism using the Caco-2 model and the pig cecum model to mimic human intestinal conditions. The most abundant imidazole alkaloid HmC 8 -Glc was neither absorbed nor transferred across cellular barriers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…On the one hand, initial transfer studies in the Caco-2 model showed that the amount of hordenine in the apical and basolateral compartments summed up was not 100%, indicating biotransformation of hordenine. On the other hand, the well-known metabolic activity of Caco-2 cells and the biotransformation of compounds observed in previous studies [ 18 ] motivated the investigation of the metabolism of hordenine.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…On the one hand, initial transfer studies in the Caco-2 model showed that the amount of hordenine in the apical and basolateral compartments summed up was not 100%, indicating biotransformation of hordenine. On the other hand, the well-known metabolic activity of Caco-2 cells and the biotransformation of compounds observed in previous studies [ 18 ] motivated the investigation of the metabolism of hordenine.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the long differentiation period of 21 d, Caco-2 cells were sensitive to incubation of compounds and sampling, resulting in an increase or decrease in TEER and thus high standard deviations. However, the high absolute TEER values of 1750 ± 260 Ω∙cm 2 (solvent treated Caco-2 cells) and 1735 ± 530 Ω∙cm 2 (hordenine treated Caco-2 cells) immediately before substance incubation indicated an intact Caco-2 monolayer suitable for transport studies [ 14 , 18 , 26 ] (S12A Fig in S1 File ). The PBCEC monolayer showed absolute TEER values above 600 Ω∙cm 2 at the beginning of the experiment, which is characteristic of an stable PBCEC barrier (S12B Fig in S1 File ) [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Braune et al reported individual differences in metabolic reactions (demethylation and dehydroxylation) and the kinetics of dehydrodiferulic acids and monomeric metabolites after incubation with human fecal suspensions . Interindividual differences between the incubation experiments regarding the formation of the metabolites were also observed in the present study as well as in former studies using the pig cecum model underlining the complexity of the individual composition of the gut microbiota and their influence on the intestinal metabolism. ,,, …”
Section: Discussionmentioning
confidence: 99%